Analysis of Students’ Mathematical Reasoning Ability in the Context of Globalization and Sustainability Using the Project Based Learning Model - Santoso, Fransiska Duitasari Wijayanti; Julie, Hongki (Jurnal Pendidikan MIPA, 2023)
Abstract: The purpose of this study is to describe the steps for planning a project-based learning (PjBL) model in teaching Mathematics in grade X in the global context of Globalization and Sustainability and describe how students' mathematical reasoning abilities are after experiencing learning using the PjBL model. The type of research used in this research is design research. In this study, researchers designed a hypothetical learning trajectory (HLT) to teach Mathematics using the PjBL model in the context of planning to build a house. The stages of the research carried out were making the initial design, conducting design trials, and conducting retrospective analysis. The research subjects were six grade X students of private high schools in Yogyakarta who used the IB (International Baccalaureate) curriculum. The data collection instruments used by the researcher were field note sheets, written test sheets in the form of worksheets containing project questions, and structured interview sheets. From this study, the results obtained were that five students were able to use mathematical reasoning to complete the construction planning project of a house. Four students have been able to check the correctness of the solution and make conclusions. Keywords: globalization and sustainability, project-based learning, mathematical reasoning, project-based learning, house building projects. Abstrak: Tujuan dari penelitian ini adalah untuk mendeskripsikan langkah-langkah merencanakan model pembelajaran berbasis proyek dalam pembelajaran Matematika di kelas X pada konteks global Globalization and Sustainability dan mendeskripsikan bagaimana kemampuan penalaran matematis siswa setelah mengalami pembelajaran dengan menggunakan model PjBL. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian desain (design research). Dalam penelitian ini, peneliti mendesain hypothetical learning trajectory (HLT) untuk membelajarkan Matematika menggunakan model PjBL dengan konteks merencanakan pembangunan sebuah rumah. Tahap-tahap penelitian yang dilakukan adalah membuat desain awal, melakukan uji coba desain serta melakukan analisis retrospektif. Subjek penelitian adalah enam siswa kelas X SMA swasta di Yogyakarta yang menggunakan kurikulum IB (International Baccalaureate). Instrumen pengumpulan data yang digunakan peneliti adalah lembar catatan lapangan, lembar tes tertulis yang berupa lembar kerja yang berisi pertanyaan proyek, dan lembar wawancara terstruktur. Dari penelitian ini, diperoleh hasil bahwa lima siswa sudah mampu menggunakan penalaran matematis untuk menyelesaikan pembuatan proyek perencanaan pembangunan sebuah rumah. Empat siswa sudah mampu untuk memeriksa kebenaran solusi dan membuat kesimpulan.  Kata kunci: globalization and sustainability, pembelajaran berbasis proyek, penalaran matematis, projet-based learning, proyek pembangunan rumah. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp753-768